THE INFLUENCE OF FINANCIAL LITERACY, LIFESTYLE, AND SOCIAL ENVIRONMENT ON STUDENT FINANCIAL BEHAVIOR - Yulia Wiranti; Goso Goso; Muh. Halim (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to determine the influence of financial literacy, lifestyle, and social environment on the financial behavior of management study program students at the faculty of economics and business at the University of Muhammadiyah Palopo. The method used in this study is quantitative. The sample used in this study consisted of 84 respondents. Sample determination using purposeful sampling Data were collected using the questionnaire dissemination method via Google links and analyzed using multiple linear regression analysis tests. The data was processed using IBM SPSS 25. The results of this study show that financial literacy and the social environment have a positive and significant effect on student financial behavior. Meanwhile, lifestyle has a negative and significant influence on students' financial behavior. The conclusion in this study is that there is an influence of financial literacy, lifestyle, and social environment on the financial behavior of management study program students at the faculty of economics and business at the University of Muhammadiyah Palopo.